Effect of a strength or hypertrophy training protocol, each performed using two different modes of resistance, on biomechanical, biochemical and anthropometric parameters - Staniszewski, M.; Mastalerz, A.; Urbanik, C. (Biology of Sport, 2020)
The study aimed to analyse the effectiveness of two variants of 8-week strength training (hypertrophy, strength) with different modes of resistance. Healthy male subjects (n=75) were allocated to five groups of equal size: hypertrophy training with a variable cam (Hyp-Cam), hypertrophy training with disc plates (Hyp-Disc), maximal strength training with a variable cam (Str-Cam), maximal strength training with disc plates (Str-Disc), and a control group (CG). The Hyp-Cam and Str-Cam groups trained with a machine where the load was adjusted to the strength capabilities of the elbow flexors. The Hyp-Disc and Str-Disc groups trained on a separate machine in which a load was applied with disc plates. The CG did not train. All groups were assessed for changes and differences in one-repetition (1RM) lifts, isokinetic muscle torque, arm circumference and arm skinfold thickness, and plasma creatine kinase (CK) activity. Within the 8-week training period the 1RM increased (p<.001) in all groups by over 20%, without significant between-group differences. Muscle torque increased significantly (p<.001) only in the Hyp-Cam group (by 13.7%). Arm circumference at rest increased by 1.7 cm (p<.001) and 1.1 cm (p<.001) in the Hyp-Cam and Hyp-Disc groups, respectively, but not in the Str-Cam (0.3 cm; p>.05) or Str-Disc (0.2 cm; p>.05) group. Skinfold thickness of the biceps and triceps decreased more within the 8-week period in Str-Cam (by 1.1 and 2.1 cm; p<.001 and p<.001 respectively) and Str-Disc (0.7 and 1.5 cm; p<.001 and p<.01 respectively) than in Hyp-Cam (by 0.4 and 1.8 cm; p>.05 and p<.01 respectively) and Hyp-Disc groups (by 0.2 and 1.4 cm; p>.05 and p<.05 respectively). CK activity was significantly (p<.05) elevated in each training group except Hyp-Cam (p>.05). The 8-week hypertrophy training with a variable cam results in greater peak muscle torque improvement than in the other examined protocols, with an insignificant increase in training-induced muscle damage indices.